Pengaruh Luas Lahan, Umur Tanaman, Dampak Kebakaran Hutan, Tenaga Kerja Dan Pupuk Terhadap Produksi Perkebunan Kelapa Sawit Rakyat Di Kecamatan Kumpeh Kabupaten Muaro Jambi (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
Muaro Jambi Regency is one of the main centers of smallholder oil palm plantations that plays an important role in the economy of Jambi Province through its contribution to crude palm oil (CPO) exports and tax revenues. This study aims to analyze farmer characteristics and the effects of land area (X1), plant age (X2), forest and land fire impacts (X3), labor (X4), and fertilizer use (X5) on the production of fresh fruit bunches (FFB) of smallholder oil palm in Kumpeh District. This study used a descriptive quantitative approach with primary data collected through a survey of 139 respondents and analyzed using multiple linear regression with the help of SPSS version 25. The results show that the average characteristics of farmers include an age of 44 years, an average of 2 dependents, land area of 2 hectares, plant age of 10 years, high fire impact scores, labor use of 2 workers, fertilizer use of 1,120 kg, and production of 20,000 kg. The regression results indicate that land area, plant age, and fertilizer use have a significant effect on production, while labor and forest and land fires do not have a significant effect on smallholder oil palm production.